2018
DOI: 10.1111/pbr.12611
|View full text |Cite
|
Sign up to set email alerts
|

Detection and validation of QTLs associated with seed longevity in rice (Oryza sativa L.)

Abstract: Seed longevity in rice is a major determinant in seed production and germplasm preservation. In this paper, a recombinant inbred line (RIL) population consisting of 172 lines derived from the cross between Xiang743 and ‘Katy’ was used to map quantitative trait loci (QTLs) for seed longevity (SL) after seed storage for 18 and 30 months under ambient conditions. Two putative QTLs, qSL‐2 and qSL‐8, were detected and located on chromosomes 2 and 8, respectively. qSL‐2 is an allele from Xiang743 allele and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Quantitative trait loci (QTLs) regulating the vigor, the longevity, and other quality‐related characteristics of seeds have been identified in rice (Li et al ). Two putative QTLs, qSL‐2 and qSL‐8 , located on chromosomes 2 and 8, respectively, increase seed longevity (Liu et al ). Glutathione‐related proteins, DNA damage repair proteins, and a putative late embryogenesis abundant (LEA) protein in two hybrid rice cultivars, IIYou998 and BoYou998, with different seed vigor exhibit different degrees of change during seed storage.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait loci (QTLs) regulating the vigor, the longevity, and other quality‐related characteristics of seeds have been identified in rice (Li et al ). Two putative QTLs, qSL‐2 and qSL‐8 , located on chromosomes 2 and 8, respectively, increase seed longevity (Liu et al ). Glutathione‐related proteins, DNA damage repair proteins, and a putative late embryogenesis abundant (LEA) protein in two hybrid rice cultivars, IIYou998 and BoYou998, with different seed vigor exhibit different degrees of change during seed storage.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, more than 70 quantitative trait loci (QTLs) controlling seed storability have been identified by genetic segregating populations under either natural or artificial aging in rice [ 4 , 8 , 9 , 10 , 11 , 12 , 13 , 29 , 30 ]. In this study, we identified nine new QTLs for rice seed storability by GWAS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For more detail we refer the reader to recent excellent reviews describing the protective factors involved in longevity [7,9,14,15]. Longevity is a multifactorial trait, evident from the multiple genetic factors have been identified using Quantitative trait locus (QTL) and Genome-Wide Association Study (GWAS) approaches using historical data from long-term storage or conditions that accelerate seed ageing in a range of crops such as wheat [17,18], soybean [19,20], oilseed rape [21][22][23], maize [24], rice [25][26][27], barley [28], tobacco [29], lettuce [30] and Arabidopsis [16]. In these studies, different storage / aging protocols have been used, giving rise do different QTL, which complicates a comparative analysis of the data.…”
Section: Seed Longevity In a Nutshellmentioning
confidence: 99%